Pendekatan Maqāṣid al-Qur’an dan Maqāṣid Shariah dalam Pembelajaran al-Qur’an Hadis di Madrasah Aliyah - Tiara Wardatutsaniyah; Hanun Asrohah; Husniyatus Salamah Zainiyati (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2026)
Contemporary Islamic education faces the challenge of moving beyond literalist and rigid approaches toward contextual learning. This study addresses this issue by formulating a synergistic framework that integrates maqāṣid Al-Qur’an (textual divine objectives) and maqāṣid al-sharī‘ah (five essential preserves of human interest) into Qur'an-Hadith learning. Employing a qualitative research design with a conceptual analysis approach, data were gathered through document analysis of classical-contemporary hermeneutical literature and the standard Madrasah Aliyah Qur'an-Hadith curriculum. The study reveals that synthesizing both maqāṣid dimensions creates a holistic pedagogical framework. While maqāṣid Al-Qur’an unlocks the intrinsic wisdom of textual verses and prophetic traditions, maqāṣid al-sharī‘ah categorizes these messages into structured societal preservation goals (faith, life, intellect, lineage, and wealth). Consequently, learning methods shift from passive memorization to inquiry-based, problem-solving, and reflective models. The impact of this synergy is the cultivation of a maqāṣidi pedagogical disposition, enabling students to bridge sacred texts with modern realities. However, as a conceptual inquiry, this study is limited by the absence of empirical classroom implementation. In conclusion, integrating maqāṣid Al-Qur’an and maqāṣid al-sharī‘ah transforms Qur'an-Hadith instruction into a dynamic, relevant, and value-oriented educational paradigm